Pelatihan Perancangan Teknologi Bel Sekolah Otomatis Berbasis Mikrokontroler di Desa Gambiran - Aisa, Aufia; Al Faris, Hasan Bisri Isa; Nashoih, Afif Kholisun; Sa’diyah, Khalimatus; Handy, Arya Dhiva; Noviana, Dwi; Mardani, Mohamad (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The lack of public understanding regarding how to design, assemble and regulate automatic school bells is the basis for holding training on designing microcontroller-based devices with the aim of providing knowledge and real experience in designing, building and operating technological systems that can become the potential for creative and innovative villages. Participants in this activity were 8 teenagers from the Gambiran Village Youth Organization. This training will be held on September 2, 2023 at 09.00 WIB at the Gambiran Village hall, Mojoagung District, Jombang Regency. The resource person in this training was one of the lecturers at K.H.A University. Wahab Hasbullah, namely Mr. Hasan Bisri Isa Al Faris, S.Kom. The approach method for community service activities in this program uses the CBR (Community Based Research) method. As a result of this training activity, participants know how to design, assemble and set up an automatic school bell which is relatively easy. This training received a good and positive response as evidenced by the community satisfaction through the results of the questionnaire after participating in the training which reached 79.2% which was classified as